Sense of self and experiences of faith among college students with sensory disabilities - Fabula, Jennifer B.; Oael, Irene C.; Muega, Maricris B. Acido; Bustos, Marie Therese Angeline P.; Cacho, Rebecca G.; Magtoto, Frances Olivia M. (Quezon City College of Education, University of the Philippine Diliman, 2022)
: Faith conversation is an essential source of spiritual connections, community, companionship, and support for people with disabilities. Sharing, reflecting, and deepening experiences through faith communities bring positivity and well-being. However, faith communities often express uncertainty on how to support meaningful participation for people with disabilities. This qualitative study aimed to explore the experiences of faith and sense of self among college students with sensory disabilities and how such perspectives engender a framework for developing programs for learners with special needs. It sought to determine how the participants experience, conceptualize and develop faith and a sense of self. It employed the grounded theory approach, precisely the constructivist method. Convenient purposive sampling was used to identify the participants. The instrument was a customized interview questionnaire, developed through the guidance of Special Education professors and pilot tested with students with similar interests as those who participated in the research. Four themes emerged through coding, categorizing, and theming: natural, supernatural, certainty, and ambiguity, generating the theory of sustaining faith to experience a sense of certainty and finding meaning in life. Recommendations include designing curricula, programs, or services in special education that integrate faith conversations to build a sense of self and achieve holistic learning.
Thesis
Includes bibliographic references (90-120 leaves)
Keywords: Sensory disorders; College Students with disabilities -- Education -- Philippines; Self-perception.; Faith; Special education -- Philippines